Advanced stimulation and dog behavior analysis system - Stojanovic, Milan; Stevanovic, Dejan; Stosovic, Slavimir (Serbian journal of electrical engineering, 2025)
This paper describes a system for analyzing the behavior of a hunting dog using the detection of the dog?s barking and its speed of movement, as well as a system for sound and vibration stimulation of the dog and LED module. These systems are part of a more complex system for tracking hunting dogs that enables hunters to monitor the movement and behavior of their dog during the hunt. Monitoring a dog?s barking provides critical insight during a hunt, especially when the dog is out of sight and pursuing game. By tracking the number of barks per minute, the hunter can determine whether the dog is actively in pursuit. If the hunter needs the dog to return or to stop chasing prey, they can issue an audible or vibratory command, provided the dog has been adequately trained. Detecting the dog?s movement speed is equally important in bird hunting, since a dog freezes in place when it locates a bird. The GPS module can pinpoint the dog?s location but cannot reveal its behavior at that spot.